The response of breast cancer cells to in vitro simulated hormonetherapy and immunotherapy - Gil, Jacqueline Ferreira (My University, 2015)
Treatment of hormone-dependent breast tumours is typically conducted using hormone-therapy, with NK cell immunotherapy a novel modality. In this study, the effects of hormone-therapy and combined hormone-therapy with immunotherapy in MCF-7 breast cancer cells was investigated. A hormone pre-treatment of 17β-oestradiol and progesterone was performed to simulate the in vivo microenvironment. Subsequently cells were treated with the hormone-therapy drugs Anastrozole or RU486 alone, or with continued hormone simulation. Combined therapy was conducted with in vitro activated NK cells co-cultured with MCF-7 cells undergoing hormone-therapy. Biomarkers ERα, PR and MUC1 were immunolocalised and expression analysed qualitatively, and quantitatively using image analysis software. Hormone pre-treatment reduced biomarker expression, stressing the importance of hormone environment simulation for in vitro experimentation. Hormone-therapy increased cytoplasmic ERα and decreased PR expression. Anastrozole increased MUC1 and RU486 decreased nuclear MUC1. With continued hormone simulation, Anastrozole further decreased all biomarkers whereas RU486 decreased ERα, increased PR expression with variable effects on MUC1 expression. RU486 induced MUC1/PR and MUC1/ERα correlation, which, under continued hormone simulation, was maintained in the nucleus only. Anastrozole induced MUC1/PR correlation in the cytoplasm which was maintained under continued hormone simulation. Hormone-therapy also induced a decrease in apoptosis, with continued hormone simulation abrogating Anastrozole induced apoptosis. While hormone-therapy did not increase proliferation, the associated changes observed in biomarker expression are linked with tumour progression indicating that short-term treatment may be detrimental for overall survival. Combined NK cell immunotherapy resulted in decreased PR, while ERα and MUC1 expression increased in a hormone-dependent manner. Biomarker correlation was evident, albeit reduced with continued hormone simulation. Independently of hormone-therapy and hormone stimulation, immunotherapy reduced apoptosis, contrary to expectation. Proliferation was marginally reduced by immunotherapy. The results indicate that immune cell function is inhibited by interaction with tumour cells, an effect that hormone-therapy cannot abrogate. Furthermore, that this study shows treatment alters both nuclear and cytoplasmic expression of biomarkers, indicates that diagnostic procedures should consider both cellular compartments in tumour progression. It is further shown that qualitative analysis of biomarker expression is not always validated by quantitative analysis, with the latter proposed as a more objective and precise method to be used diagnostically.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine Faculty of Health Sciences University of the Witwatersrand Johannesburg 2015
Keywords: BLID protein, human; Fertilization in Vitro; In Vitro Techniques/therapy